Organizational Sources of Academic Burnout Among Teaching Students – Towards a Sustainable Fit - Chirkowska-Smolak, Teresa; Garbacik, Żaneta; Piorunek, Magdalena; Górecki, Tomasz; Drabik-Podgórna , Violetta; Kławsiuć-Zduńczyk, Anna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2025)
The issue of student burnout is gaining prominence in discussions regarding the sustainability of the higher education environment. This quantitative research aimed to delineate burnout profiles among Polish students enrolled in education-related programs based on exhaustion, cynicism, and inefficacy, and examine these profiles concerning their academic fit – spanning workload, autonomy, peer relationships, teaching quality, institutional values, and administration. Utilizing the Maslach Burnout Inventory – General Scale for Students (MBI-GSS) and the Areas of Academic Life Scale (AALS), we surveyed 1,519 students from educational faculties in Poland to identify prevalent burnout profiles and their correlations with six dimensions of academic life. Our analysis discerned four burnout profiles, from minimal to severe, revealing that a significant portion of students are at least at risk of burnout, with notably, one in ten exhibiting a “High burnout, critical concern” profile. The analysis revealed patterns in how burnout profiles were related to specific dimensions of academic life. Our findings reveal the multifaceted nature of student burnout and point to the crucial role of aligning academic environmental factors. Supporting academic sustainability requires a nuanced understanding of these elements to create a more supportive university environment.